Distribution and Discharge of Dissolved Methane in the Middle Okinawa Trough, East China Sea - Zhang, Xianrong; Sun, Zhilei; Wang, Libo; Zhang, Xilin; Zhai, Bin; Xu, Cuiling; Geng, Wei; Cao, Hong; Yin, Xijie; Wu, Nengyou (Frontiers in Earth Science, 2020)
Widespread seepage of methane from seafloor sediments on continental margins may plays an important role in methane cycles in the ocean and even atmosphere. However, the distribution pattern of methane seepage has not been fully understood. To assess the methane distribution characteristics and its influence on the atmosphere, we report methane emissions from the shelf and west slope of the middle back-arc Okinawa Trough (OT), East China Sea. The result shows that the methane concentrations are obviously heterogeneity. The highest value, which is more than 10 times of the background concentration, presented in the north of the study area near the cold seep. The source of the methane is not only dominated by the cold seepage input, but also related to in situ aerobic methane production, physical advective on continental shelf and hydrothermal fluid. Furthermore, the sea-to-air flux of methane throughout the study area (up to 116 μmol m-2d-1) is significantly higher than that in many other continental shelf waters and global seep sites, indicating that this region is an active CH4 emission area. Our findings demonstrate that methane discharged from both cold seepage and hydrothermal vents has a significant influence on the methane cycle in the OT, providing a new insight for methane budget of back-arc basin.